Bideleux, R. and I.Jeffries, The Balkans: A Post-Communist History (London:2007: Routledge). A Comment. - Jakovina, Tvrtko (2009)
Comment of R. Bideleux and I. Jeffries book: The Balkans: A Post-Communist History.
Projekt MZOS
ENG